The The Effectiveness of Myofascial Release Technique and Self Exercise in Reducing Pain & Disability in Elderly with Myofascial Pain Syndrome - Saraswati, Putu Ayu Sita; Thanaya, Sayu Aryantari Putri; Vittala, Govinda (Poltekkes Kemenkes Surakarta, 2024)
Background: Neck pain is a major public health problem, especially for the elderly. One cause of neck pain is myofascial pain syndrome. Myofascial pain syndrome is characterized by the presence of trigger points that arise from the junction bands of muscle fibers. Three studies found that the prevalence of neck pain in the elderly was between 8.8% and 11.6%. Chronic neck pain causes increased muscle tone, decreased joint range of motion, functional impairment and activities of daily living, and decreased quality of life in the elderly. This study aimed to compare the effectiveness of combining myofascial release technique and ultrasound with self-exercise and ultrasound in reducing pain and neck disability for the elderly. Methods: This experimental study used a randomized pre- and post-test control group design. The variables in this study were pain and neck disability. The participants were 24 people who were divided into Group 1 with myofascial release technique (n = 12) and Group 2 with self-exercise (n = 12). The intervention was given 3 times per week for 4 weeks. Results: The results showed that neck disability significantly decreased before and after the intervention in both groups (p<0.001). There was also a significant difference between the two groups. Conclusion: Myofascial release technique and self-exercise are effective in reducing neck pain and disability in the elderly with myofascial pain syndrome. However, the combination of ultrasound and myofascial release technique is more effective than ultrasound and self-exercise in reducing neck pain and disability in the elderly with myofascial pain syndrome.